Experimental investigation on the power and thrust characteristics of a wind turbine model subjected to surge and sway motions. (January 2022) - Meng, Haoran; Su, Hao; Guo, Jia; Qu, Timing; Lei, Liping
Abstract: In the present study, wind tunnel experiments were performed to investigate the power and thrust characteristics of a wind turbine model subjected to a variety of surge and sway motions. The turbine model was mounted on a translational stage to simulate the surge and sway motions at prescribed amplitudes and frequencies. The power output and rotor thrust were measured in each sets of the motion frequencies and amplitudes, respectively; and the measurements were also performed in a base-fixed turbine for comparison. Results show that the surge and sway motions with various amplitudes and frequencies all have slight impact on the mean power output and mean rotor thrust of a wind turbine. However, the rotor thrust fluctuations of the surging turbine, not only appeared significantly higher than those of the swaying turbine and base-fixed turbine at the same sets of amplitudes and frequencies, but also increased with the surge frequency and surge amplitude. Moreover, for both the surging and swaying turbine, the rotor thrust fluctuated with the same period as the surge and sway motions, respectively; and the power spectral density of the rotor thrust both exhibited a peak at the motion frequency and its odd multiple frequencies. Highlights: Turbine power and thrust characteristics under surge and sway motions were studied. Motions had slight effect on mean turbine power and thrust in various conditions. Thrust fluctuations of surging turbine were higher than swaying and fixed turbine. Surging turbine thrust fluctuations increased with surge frequency and amplitude. The PSD of thrust for surging and swaying turbine peaked at motion frequency.